Susceptibility of developmental stages of Tetranychus urticae (Acari: Tetranychidae) to infection by Beauveria bassiana and Metarhizium anisopliae (Hypocreales: Clavicipitaceae). (15th August 2014) - Bugeme, David M.; Knapp, Markus; Boga, Hamadi I.; Ekesi, Sunday; Maniania, Nguya K.
<x content-type="archive" xml:space="preserve">Abstract</x> In the present study, the susceptibility of different developmental stages (eggs, larvae, protonymphs, deutonymphs and adults) of Tetranychus urticae Koch to the entomopathogenic fungi Beauveria bassiana (Balsamo-Crivelli) Vuillemin and Metarhizium anisopliae (Metchnikoff) Sorokin was evaluated in the laboratory. At each developmental stage, four concentrations (3 × 105, 1 × 106, 3 × 106 and 1 × 107 conidia/ml) of both fungi were sprayed. Egg viability and motile-stage mortality varied among the fungal isolates and conidial concentrations. The highest conidial concentration (1 × 107 conidia/ml) significantly reduced the viability of eggs and increased the mortality of motile stages. However, deutonymphs and adults were more susceptible to fungal infection than larvae and protonymphs. The lethal concentration values to 50% (LC50) and 90% mortality (LC90) varied with the fungal isolates and developmental stages. The results show the prospects of B. bassiana and M. anisopliae for the control of T. urticae.